DEVELOPMENT OF INTERCULTURAL COMMUNICATION COMPETENCE OF NONPROFESSIONAL STUDENTS IN THE PROCESS OF ENGLISH LANGUAGE EDUCATION WITH THE HELP OF PODCASTING - Ismoilova Zarifa Abduqaxxorovna (Western European Studies, 2025)
The development of intercultural communication competence (ICC) is critical in today’s globalized world, particularly for non-professional students who are learning English as a second language. This article explores the potential of podcasting as an effective tool for fostering intercultural communication skills in non-professional students within the context of English language education. By examining how podcasts, as accessible and engaging digital media, can bridge cultural gaps and enhance language acquisition, the study highlights their contribution to both language learning and the cultivation of ICC. The article discusses the pedagogical advantages of podcasts, such as promoting authentic listening experiences, exposing students to diverse cultural contexts, and facilitating independent learning. It further offers practical strategies for integrating podcasting into English language courses and suggests areas for further research
Keywords: Intercultural communication competence; non-professional students; English language education